Brazil: History and Trends in Mathematics Education - D’Ambrosio, Beatriz S.; Martins, Juliana [UNESP]; de Oliveira Santos, Viviane [UNESP] (World Scientific Publishing, 2014)
This chapter begins with a brief history of mathematics education in Brazil, contextualized within the socio-political and educational events in the country. Research in ethnomathematics and mathematical modeling provide the foundation for curriculum reform and teacher preparation initiatives that strive to achieve greater social justice and equity for Brazilian children.
Keywords: Equity; Ethnomathematics; History of mathematics education; Mathematical modeling; Mathematics education; Social justice